Use of Masquelet's technique for treating the first metatarsophalangeal joint in cases of gout combined with a massive bone defect. Issue 2 (April 2018) - Liu, Feng; Huang, Ruo-kun; Xie, Ming; Pan, Hao; Zhao, Jing-jing; Lei, Bo
Highlights: To examine the safety and efficacy of Masquelet's technique as a surgical method for treating the first metatarsophalangeal joint in cases of gout accompanied by a massive bone defect. During the first stage of Masquelet's technique, we removed the tophus and infused that area with artificial bone cement that contained antibiotics. Two months later, we performed the second stage, in which the prosthesis was replaced with iliac cancellous bone, and the operated area was stabilized via locking plate fixation. Abstract: Background: To examine the safety and efficacy of Masquelet's technique as a surgical method for treating the first metatarsophalangeal joint in cases of gout accompanied by a massive bone defect. Methods: From January 2010 to January 2016, eleven patients (7 males and 4 females; mean age 33.1 years; range, 23–43 years) received surgical treatment for a first metatarsophalangeal joint tophus which caused a serious bone defect. The first metatarsophalangeal bone defects ranged from 3–6 cm, or nearly 50% of the length of normal bone. During the first stage of Masquelet's technique, we removed the tophus and infused that area with bone cement that contained antibiotics. Two months later, we performed the second stage, in which the prosthesis was replaced with iliac cancellous bone, and the operated area was stabilized via locking plate fixation. Results: All of the surgeries were successful, and the 11 patients were followed up for an average of 10.9 months. Postoperative evaluations showed that 10 of the 11 patients healed between 9 and 14 days after the initial surgery. Bone fusion occurred between 2.3 and 3.6 months after the operation, and the average healing time was 3.0 months. One foot wound became infected, but healed after vacuum aspiration. When the American Association of Foot and Ankle Surgery Maryland Foot scoring system was used to evaluate the foot function of the 11 patients prior to surgery, all 11 patients were graded as "failures." Following surgery, 2 patients were graded excellent, 5 were good, 3 were fair, and only 1 patient failed. The total combined excellent and good rate was 63.6%. The total mean Maryland scores pre- and post-surgery were 27.8 points and 74.1 points, respectively; thus the average patient score increased by 46.3 points. Conclusions: Joints with advanced tophus nodules develop segmental bone defects. Masquelet's technique is an effective method for treating such nodules and their associated bone defects.